Data-Driven Smart Home System for Elderly People Based on Web Technologies - Seo, Daeil; Yoo, Byounghyun; Ko, Heedong (DISTRIBUTED, AMBIENT AND PERVASIVE INTERACTIONS, (DAPI 2016), 2016)
The proportion of elderly people over 65 years old has rapidly increased, and social costs related to aging population problems have grown globally. The governments want to reduce these social costs through advanced technologies. The physician or medical center evaluates health conditions from the reports of elderly people. However, self-reports are often inaccurate, and sometimes reports by family or caregivers can be more accurate. To solve these problems, an evaluated objective method based on sensor data is needed. In this paper, we propose a data-driven smart home system that uses web technologies for connecting sensors and actuators. The proposed system provides a method of monitoring elderly people's daily activities using commercial sensors to register recognizable activities easily. In addition, it controls actuators in the home by using user-defined rules and shows a summary of elderly people's activities to monitor them.